Evaluation of Social Media Utilization by Academic Plastic Surgery Programs during the COVID-19 Pandemic. Issue 5 (November 2021) - Shiah, Eric; Laikhter, Elizabeth; Manstein, Samuel M.; Comer, Carly D.; Shen, Abra H.; Lin, Samuel J.
Abstract : Background: In response to the cancellation of away rotations and the shift to virtual interviews due to the coronavirus disease of 2019 (COVID-19) pandemic, residency programs have pursued other methods of sharing program details, most notably with the use of social media. This study aimed to evaluate the extent of social media utilization in the setting of the COVID-19 pandemic by plastic surgery residency programs. Methods: Instagram, Twitter, and Facebook accounts of plastic surgery programs, program directors, and chiefs were identified. Number of followers, total posts, and posts since March 1, 2020, were extracted. Account content was categorized as informational, social, operative, research, self-promotional, guest lecture, education, or other. Spearman's coefficient was used to determine correlations among account data. Differences among regions and program pathways were evaluated using the Kruskal-Wallis test. Results: Since March 1, 2020, 17 Instagram, five Twitter, and three Facebook accounts have been created. Instagram was most widely used and followed (1720 posts, 1235.7 ± 735.9 followers) compared with Twitter (722 tweets, 325.6 ± 451.0 followers) and Facebook (430 posts, 338.3 ± 363.3 followers). Although the majority of content was informational (45.1 percent), Instagram contained more social content (21 percent), Twitter contained more research (21 percent), and Facebook contained more self-promotional content (25 percent). Integrated-only programs on average posted more on Instagram (21.5 ± 15.1 posts) than did independent-only programs (9.4 ± 8.5 posts), and post volume moderately correlated with number of followers. There were no statistically significant differences among regional means. Conclusion: Plastic surgery residency programs have incorporated social media into their recruitment strategies and will likely continue to increase and diversify their posts to effectively engage with future applicants.